Trying to understand the different pieces of the construct validity puzzle of assessment centers: An examination of assessor and assessee effects - LIEVENS, Filip (Institutional Knowledge at Singapore Management University, 2002)
This study examined the effects of assessor-related factors (i.e., type of assessor) and assessee-related factors (i.e., type of assessee profile) on the construct validity of assessment center ratings. In particular, 3 types of assessors (26 industrial/organizational [I/O] psychologists, 20 managers, and 27 students), rated assessee performances that varied according to cross-exercise consistency (i.e., relatively inconsistent vs. relatively consistent) and dimension differentiation (relatively undifferentiated vs. relatively differentiated). Construct validity evidence was established for only one assessee profile and only in the I/O psychologist and managerial samples. More generally, these results indicate that 3 factors (poor design, assessor unreliability, and especially cross-situational inconsistent assessee performances) may explain why construct validity evidence is often not established in operational assessment centers.